POSSIBILITIES OF DEVELOPING MOTIVATION FOR LEARNING AMONG STUDENTS OF THE UNIVERSITY OF PRISTINA WITH TEMPORARY HEADQUARTERS IN KOSOVSKA MITROVICA (Heritage, 2021)
he paper strives to consider the intensity and structure of motivation for studying among undergraduates of the University of Priština in Kosovska Mitrovica, as well as to check whether there are differences in the intensity of intrinsic and extrinsic motivation among undergraduates of different faculties. In addition, drawing on the Theory of Self-Determination of Edward Deci and Richard Ryan, we were interested in the structure of motivation for studying in two socio-cultural areas: Serbia and Croatia. The research was conducted during the summer semester of 2017 on the premises of five faculties. The Thomas-Miller scale was used to examine motivation for studying. The most intense individual motivator for studying is «I am studying, because I will be able to get / find a better job», and the presence of the intrinsic factor of motivation for studying is more pronounced. The research findings have indicated that all motivators are classified into two factors, intrinsic and extrinsic ones, and account for 51.40% of the variance of the observed measurement space.Our research obtained a different structure of factors, in relation to the research results in Croatia. Motivators “... because I simply have to” and “… because I will be able to get / find a better job” have replaced affiliation, in relation to the structure of factors obtained in the Croatian sample of respondents. Both observed factors of motivation for studying are the most intense among undergraduates of the Faculty of Medicine. Undergraduates from other faculties do not differ statistically significantly in the intensity of both motivational factors.
Keywords: motivation for studying, undergraduates, Theory of Self-Determination, Thomas-Miller scale